Predicting solvatochromic shifts and colours of a solvated organic dye: the example of nile red - Zuehlsdorff,TJ; Haynes,PD; Payne,MC; Hine,NDM (Journal of Chemical Physics, 2017)
The solvatochromic shift, as well as the change in colour of the simple organic dye nile red, is studied in two polar and two non-polar solvents in the context of large-scale time-dependent density-functional theory (TDDFT) calculations treating large parts of the solvent environment from first principles. We show that an explicit solvent representation is vital to resolve absorption peak shifts between nile red in n-hexane and toluene, as well as acetone and ethanol. The origin of the failure of implicit solvent models for these solvents is identified as being due to the strong solute-solvent interactions in form of π-stacking and hydrogen bonding in the case of toluene and ethanol. We furthermore demonstrate that the failures of the computationally inexpensive Perdew-Burke-Ernzerhof (PBE) functional in describing some features of the excited state potential energy surface of the S1 state of nile red can be corrected for in a straightforward fashion, relying only on a small number of calculations making use of more sophisticated range-separated hybrid functionals. The resulting solvatochromic shifts and predicted colours are in excellent agreement with experiment, showing the computational approach outlined in this work to yield very robust predictions of optical properties of dyes in solution.